Towards understanding participatory processes: Framework, application and results. (1st July 2015) - Hassenforder, Emeline; Smajgl, Alex; Ward, John
Abstract: Many scholars point out that in complex and contested decision-making and planning situations, participatory processes have clear advantages over "traditional" or non-participatory processes. Improving our understanding of which participatory process elements or combination of elements contribute to specific outcomes demands a comparative diagnosis of multiple case studies based on a systematic framework. This paper describes the theoretical foundation and application of a diagnostic framework developed for the description and comparative analysis of participatory processes. The framework for the Comparison of Participatory Processes (COPP) is composed of three dimensions: context, process, and outputs outcomes and impacts. For each dimension, a list of variables is provided, with associated selectable options. The framework also requires clarification of three monitoring and evaluation elements. The COPP framework is then applied to five participatory processes across five different contexts: three located in the Mekong basin in Southeast Asia and two in eastern Africa. The goal is to test first if the framework facilitates the development of a comprehensive and clear description of participatory processes, and second, if a diagnostic step can be facilitated by applying the descriptions in a cross-comparative analysis. The paper concludes that despite a few challenges, the COPP framework is sufficiently generic to derive clear and consistent descriptions. A sample of only five case studies restricts the derivation of robust insights. Nevertheless, three testable hypothesis were derived, which would need to be tested with a much larger sample of case studies in order to substantiate the efficacy of process characteristics and attributes. Ultimately, such hypotheses and subsequent analytical efforts would contribute to the advancement of this increasingly prominent research domain. Highlights: We suggest a framework for the Comparison of Participatory Processes (COPP). Multilevel engagement is more likely to lead to outcomes. Specific participatory methods are easily replaceable. The degree of system complexity can compromise methods' effectiveness. A two-years minimum engagement span is more likely to lead to objectives' achievement.